ISOLATION OF STEROID COMPOUNDS IN THE n-HEKSANA FRACTION FROM JARUM TUJUH BILAH LEAVES EXTRACT (Leuenbergeria bleo (Kunth) D.C.) - Yuli Yana; Chairul Saleh; Noor Hindryawati (JURNAL KIMIA MULAWARMAN, 2019)
This study aims to find secondary metabolites isolated from the leaves of the Jarum Tujuh Bilah (Leuenbergeria bleo (Kunth) D.C.). The method used was maceration, fractionation and column chromatography and was identified using Fourier Transformra Infra Red (FT-IR). The phytochemical preliminary test of the n-hexane fraction contains the steroid secondary metabolite compound. The results of column chromatography produced 75 vial bottles which were then identified by thin layer chromatography and produced 8 combined fractions (A-H fraction) based on the similarity of characterization, from the 8 fractions D and E forming yellow crystals. The yellow crystals formed are then cleaned and recrystallized to produce 11.7 mg white amorphous crystals. Compounds are characterized by FTIR spectrometers. Based on FTIR analysis, isolates showed IR spectrum Î» max cm-1: 3375; 2927,98; 2852,18; 1680; 1462,51; 1376.81; 1329.74; 1043,92; 1022.02 and 956.27. Based on the results obtained by isolates, it is suspected that the compound is a steroid sterol.